Effect of Green Tea Extract as Antioxidant on Shear Bond Strength of Resin Composite to in-Office and Home-Bleached Enamel - Sharafeddin F; Farshad F; Azarian B; Afshari A (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Shear bond strength (SBS) of home and office bleached enamel will be compromised by immediate application of composite restoration. Antioxidant agent may overcome this problem. Objectives: This in vitro study assessed the effect of green tea extract on shear bond strength of resin composite to in-office and home-bleached enamel. Materials and Methods: In this experimental study, 40 extracted intact human incisors were embedded in cylindrical acrylic resin blocks (2.5 ×1.5 cm), with the coronal portion above the cemento enamel junction out of the block. Then, after bleaching labial enamel surfaces of 20 teeth with 15% carbamide peroxide 6 hours a day for 5 days, they were randomly divided into two groups: A1 and A2 (n = 10), depending upon whether or not they are treated with antioxidant. Labial enamel surfaces of the remaining 20 teeth were bleached with 38% hydrogen peroxide before being randomly divided into groups B1 and B2 (n = 10), again depending on whether or not the antioxidant was used in their treatment . The experimental groups (A2,B2) were treated with 5% solution of green tea extract before resin composite restoration was done by a cylindrical Teflon mould (5×2 mm). Shear bond strength of the specimens was tested under a universal testing machine (Zwick/Roell Z020). The SBS data were analyzed by using One-way ANOVA and Tukey HSD tests (p < 0.05). Results: There were no statistically significant differences between shear bond strength of the control group (A1) and treated group (A2) but there were statistically significant differences between the groups B1 and B2 (p < 0.05). Conclusions: Application of antioxidant did not increase the shear bond strength of home-bleached enamel to resin composite but its application increased the shear bond strength of in-office bleached enamel to resin composite.